Fibrates: A Possible Treatment Option for Patients with Abdominal Aortic Aneurysm? - Naofumi Amioka; Toru Miyoshi (Biomolecules, 2022)
Abdominal aortic aneurysm (AAA) is a life-threatening disease; however, there is no established treatment for patients with AAA. Fibrates are agonists of peroxisome proliferator-activated receptor alpha (PPARα) that are widely used as therapeutic agents to treat patients with hypertriglyceridemia. They can regulate the pathogenesis of AAA in multiple ways, for example, by exerting anti-inflammatory and anti-oxidative effects and suppressing the expression of matrix metalloproteinases. Previously, basic and clinical studies have evaluated the effects of fenofibrate on AAA. In this paper, we summarize the results of these studies and discuss the problems associated with using fenofibrate as a therapeutic agent for patients with AAA. In addition, we discuss a new perspective on the regulation of AAA by PPARα agonists.